A systematic review of the effect of university positive psychology courses on student psychological wellbeing - Hobbs, Catherine; Armitage, Jessica; Hood, Bruce; Jelbert, Sarah (Frontiers in Psychology, 2022)
Educational courses that teach positive psychology interventions as part of university degree programs are becoming increasingly popular, and could potentially form part of university-wide strategies to respond to the student mental health crisis. To determine whether such courses are effective in promoting student wellbeing, we conducted a systematic review of studies across the globe investigating the effects of positive psychology courses taught within university degree programs on quantitative measures of psychological wellbeing. We searched Embase, PsychInfo, PubMed, and Web of Science electronic databases from 1998 to 2021, identifying 27 relevant studies. Most studies (85%) reported positive effects on measures of psychological wellbeing, including increased life satisfaction and happiness. However, risk of bias, assessed using the ROBINS-I tool, was moderate or serious for all studies. We tentatively suggest that university positive psychology courses could be a promising avenue for promoting student wellbeing. However, further research implementing rigorous research practices is necessary to validate reported benefits, and confirm whether such courses should form part of an evidence-based response to student wellbeing. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=224202], identifier [CRD42020224202].